INSTITUTIONAL DESIGN OF THE REGIONAL HOUSE OF REPRESENTATIVES (DPRD): LEGAL POLITICAL STUDY ON INDONESIA’S LAW NUMBER 23 OF 2014 CONCERNING REGIONAL GOVERNMENT - Tauda, Gunawan A.; Umasangaji, Amirudin; Rumkel, Nam; Istiqamallah, Nurul (Jurnal Hukum dan Peradilan, 2022)
By the promulgation of Law Number 23 of 2014 concerning Regional Government, there has been a shift in the institutional design of the Regional House of Representatives (DPRD in Bahasa Indonesia), especially in the aspects of the legislative function and its authority. There is an affirmation of the understanding of the DPRD as an element of regional government administration. In this context, the House of Representatives (DPR in Bahasa Indonesia) and the President deliberately combine the two types of power functions, the legislative and the executive, into one institution called the DPRD in the local government system in Indonesia. Shifting of institutional design above indicates that Regional Government Law is principally no longer categorizes the DPRD as a legislative agency but instead as an executive institution playing a role in supervising the implementation of Regional Government. Based on this Regulation, the theoretical interpretation of DPRD’s existence is interpreted as an executive institution running the legislative function.